Tunable microsecond dynamics of an allosteric switch regulate the activity of a AAA+ disaggregation machine - Hisham Mazal; Marija Iljina; Yoav Barak; Nadav Elad; Rina Rosenzweig; Pierre Goloubinoff; Inbal Riven; Gilad Haran (Nature Communications, 2019)
Large protein machines are tightly regulated through allosteric communication channels. Here authors use single-molecule FRET and demonstrate the involvement of ultrafast conformational dynamics in the allosteric regulation of ClpB, a hexameric AAA+ machine that rescues aggregated proteins.